Chemical Heterointerface Engineering on Hybrid Electrode Materials for Electrochemical Energy Storage. Issue 8 (17th June 2021) - Li, Wenbin; Song, Qianqian; Li, Matthew; Yuan, Yifei; Zhang, Jianhua; Wang, Ni; Yang, Zihao; Huang, Jianfeng; Lu, Jun; Li, Xifei
Abstract: The chemical heterointerfaces in hybrid electrode materials play an important role in overcoming the intrinsic drawbacks of individual materials and thus expedite the in‐depth development of electrochemical energy storage. Benefiting from the three enhancement effects of accelerating charge transport, increasing the number of storage sites, and reinforcing structural stability, the chemical heterointerfaces have attracted extensive interest and the electrochemical performances of hybrid electrode materials have been significantly optimized. In this review, recent advances regarding chemical heterointerface engineering in hybrid electrode materials are systematically summarized. Especially, the intrinsic behaviors of chemical heterointerfaces on hybrid electrode materials are refined based on built‐in electric field, van der Waals interaction, lattice mismatch and connection, electron cloud bias and chemical bond, and their combination. The strategies for introducing chemical heterointerfaces are classified into in situ local transformation, in situ growth, cosynthesis, and other strategy. The recent progress about the chemical heterointerfaces engineering specially focusing on metal‐ion batteries, supercapacitors, and Li–S batteries are introduced in detail. Furthermore, the classification and characterization of chemical heterointerfaces are briefly described. Finally, the emerging challenges and perspectives about future directions of chemical heterointerface engineering are proposed. Abstract : This work provides a new perspective to understand the intrinsic behaviors of chemical heterointerfaces on hybrid electrode materials, highlights the strategies for introducing chemical heterointerfaces, introduces the three enhancement effects of chemical heterointerfaces on electrochemical performance, and summarizes the recent progress of chemical heterointerfaces engineering in the metal‐ion batteries, supercapacitors, and Li–S batteries.